An Optimized Assay for Assessing Platelet Dense Granule Secretion Using Diluted Whole Blood. (11th September 2019) - Cho, Joseph; Mikrut, Krzysztof; Miller, Jonathan
Abstract: Assessment of dense granule secretion following agonist stimulation is an integral part of platelet function testing and can be performed in the clinical laboratory using lumi-aggregometry. A significant limitation of traditional lumi-aggregometry is the relatively large volume of blood required and the normal platelet counts needed to perform the assay, which often precludes usage of this test in pediatric and thrombocytopenic patients. By optimizing the luciferase-luciferin reaction with commercially available reagents and using a conventional lumi-aggregometer, we have developed a method that measures platelet dense granule secretion following agonist stimulation in diluted whole blood, at up to 10-fold dilutions. With the goal of developing a testing method independent of platelet count, the assay intentionally does not include specimen stirring. Direct comparison of the optimized reagents with the standard Chrono-lume reagent in 10-fold diluted whole blood showed an improved lower limit of detection for exogenously added ATP by at least one order of magnitude. We reproducibly observed dose-dependent responses in platelet ATP release using this assay upon stimulation with platelet agonists such as the thrombin receptor-activating peptide (TRAP) and the collagen receptor agonist convulxin. ATP release in 10-fold diluted whole blood, for example, was 168.6 ± 24.7 pmoles/10 7 platelets in response to 40 μM TRAP and 17.1 ± 2.9 pmoles/10 7 platelets in response to 1 nM convulxin (mean ± SEM, N = 6). Method comparisons of this assay were performed using 10-fold diluted whole blood without stirring, compared to standard methodology using undiluted platelet-rich plasma stirred at 1000 rpm. On concurrently run, matched specimens, ATP release in response to a series of agonists of varying stimulus intensity showed overall moderate concordance, with an r 2 = 0.722. Based on ATP standard curves and the observed agonist responses to date, we are hopeful that this assay may prove capable of assessing platelet dense granule release in patient blood with platelet counts as low as 20, 000/μL. Additionally, the assay requires less than 60 μL of whole blood per agonist with testing performed at two different agonist concentrations. The extended analytical range and robustness of the assay, with no need for centrifugation, offer promise that it may be useful for the assessment of platelet dense granule secretion in pediatric or thrombocytopenic patients who require assays amenable to limited blood volumes and low platelet counts.